The roles of cooperative advertising and endogenous online price discount in a dual-channel supply chain. (February 2023) - Li, Jicai; Ou, Jinwen; Cao, Bin
Abstract: Cooperative advertising and product price discount are important roles of influencing manufacturer and (online) retailer decisions in supply chains. This paper develops a model to explicitly explore the impacts of practical online price discount and different cooperative advertising modes on a dual-channel supply chain consisting of a manufacturer and an e-platform. The manufacturer can sell a product to end consumers through an offline channel and an online channel; the latter is implemented by the e-platform which charges a commission fee under an agency selling arrangement. Our results show that offering a price discount in the online channel may be not better for the manufacturer, which can be determined by a threshold policy in terms of the effect of the online price discount on the online market demand. Further, the optimal price discount level offered will remains at a relatively low level. We also show that the online price discount level is always the lowest under bilateral cooperative advertising setting, but might be the highest under unilateral cooperative advertising setting. By comparison with unilateral cooperative advertising, the increase in the manufacturer's profit under bilateral cooperative advertising is obtained by reducing the e-platform's profit. Such a "benefit-oneself-at-the-expense-of-others" method may be harmful to the total profit of the overall supply chain, which may evidently explain why bilateral cooperative advertising is rarely used in practice. Highlights: We explore the impacts of online price discounting and cooperative advertising. Whether the manufacturer offers an online price discount can be characterized as a threshold policy. The optimal price discount level is always offered at relatively low level. The manufacturer's and platform's profits may be not improved simultaneously. We explain why bilateral cooperative advertising is rarely used in practice.